Ni2Mn-layered double oxide electrodes in organic electrolyte based supercapacitors. Issue 44 (10th August 2021) - Hong, Jindui; Chen, Chunping; Siriviriyanun, Ampornphan; Crivoi, Dana-Georgiana; Holdway, Philip; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : Ni2 Mn-layered double oxide (LDO) electrode not only expands the working voltage and enhances the specific capacitance of layered double hydroxide (LDH) in the organic electrolyte but also outperforms NiO, MnO2 and their physical mixture. Abstract : The development of future mobility ( e.g. electric vehicles) requires supercapacitors with high voltage and high energy density. Conventional active carbon-based supercapacitors have almost reached their limit of energy density which is still far below the desired performance. Advanced materials, particularly metal hydroxides/oxides with tailored structure are promising supercapacitor electrodes to push the limit of energy density. To date, research has largely focused on evaluation of these materials in aqueous electrolyte, while this may enable high specific capacitance, it results in low working voltage window and poor cycle stability. Herein, we report the development of Ni2 Mn-layered double oxides (Ni2 Mn-LDOs) as mixed metal oxide-based supercapacitor electrodes for use in an organic electrolyte. Ni2 Mn-LDO obtained by calcination of [Ni0.66 Mn0.33 (OH)2 ](CO3 )0.175 · n H2 O at 400 °C produced the best performing Ni2 Mn-LDOs with high working voltage of 2.5 V and a specific capacitance of 44 F g −1 (at 1 A g −1 ). We believe the performance of the Ni2 Mn-LDOs is related to its unique porous structure, high surface area and the homogeneous mixed metal oxide network. Ni2 Mn-LDO outperforms both the single metal oxides (NiO, MnO2 ) and the equivalent physical mixture of the two oxides. We propose this performance boost arises from synergy between NiO and MnO x due to a more effective homogeneous network of NiO/MnO x domains in the Ni2 Mn-LDO. This work clearly shows the advantage of an LDO over the single component metal oxides as well as the physical mixture of mixed metal oxides and highlights the possibilities of development of further mixed metal oxides-based supercapacitors in organic electrolyte using LDH precursors.